Redefining Bean Iron Biofortification: A Review of the Evidence for Moving to a High Fe Bioavailability Approach - Glahn, Raymond P.; Noh, Hannah (Frontiers in Sustainable Food Systems, 2021)
Iron biofortification of the common bean (Phaseolus vulgaris) commenced in earnest ~18 years ago. Based on knowledge at the time, the biofortification approach for beans was simply to breed for increased Fe concentration based on 3 major assumptions: (1) The average bean Fe concentration is ~50 μg/g; (2) Higher Fe concentration results in more bioavailable Fe delivered for absorption; (3) Breeding for high Fe concentration is a trait that can be achieved through traditional breeding and is sustainable once a high Fe bean sample is released to farmers. Current research indicates that the assumptions of the high Fe breeding approach are not met in countries of East Africa, a major focus area of bean Fe biofortification. Thus, there is a need to redefine bean Fe biofortification. For assumption 1, recent research indicates that the average bean Fe concentration in East Africa is 71 μg/g, thus about 20 μg/g higher than the assumed value. For assumption 2, recent studies demonstrate that for beans higher Fe concentration does not always equate to more Fe absorption. Finally, for assumption 3, studies show a strong environment and genotype by environment effect on Fe concentration, thus making it difficult to develop and sustain high Fe concentrations. This paper provides an examination of the available evidence related to the above assumptions, and offers an alternative approach utilizing tools that focus on Fe bioavailability to redefine Fe biofortification of the common bean.